2010
DOI: 10.1002/etc.260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of black carbon and chemical planarity on bioavailability of sediment‐associated contaminants

Abstract: Black carbon (BC) and chemical properties may play a significant role in defining the bioavailability of hydrophobic organic compounds (HOCs) in sediment. In the current study, bioavailability of four HOCs with differing planarity was determined in sediments amended with two types of BC (soot and charcoal) at different concentrations by matrix solid-phase microextraction (matrix-SPME) and bioaccumulation testing using the freshwater oligochaete Lumbriculus variegatus. Furthermore, the applicability of the matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…Fleming et al (1998) reported that different types of OC (peat or a-cellulose) significantly affected permethrin toxicity to Chironomus riparius at a constant OC content. In contrast, previous studies with spiked sediment showed BC significantly reduced the bioavailability of planar compounds, like benzo[a]pyrene, but had little effect on non-planar compounds, like permethrin (Pehkonen et al, 2010;Yang et al, 2009). The discrepancy among these studies may be due to the difference in OC types and sediment aging time.…”
Section: Reduced Bioavailability and Toxicitycontrasting
confidence: 66%
“…Fleming et al (1998) reported that different types of OC (peat or a-cellulose) significantly affected permethrin toxicity to Chironomus riparius at a constant OC content. In contrast, previous studies with spiked sediment showed BC significantly reduced the bioavailability of planar compounds, like benzo[a]pyrene, but had little effect on non-planar compounds, like permethrin (Pehkonen et al, 2010;Yang et al, 2009). The discrepancy among these studies may be due to the difference in OC types and sediment aging time.…”
Section: Reduced Bioavailability and Toxicitycontrasting
confidence: 66%
“…21 Conversely, other studies have compared C f to chemical residues in organisms at the completion of exposure when the fiber and the organism have reached equilibrium and steady state, respectively. 3,6,22,23,31 Due to the different uptake rates for the fibers and organisms, relationships established at equilibrium are more likely to be consistent. Nevertheless, a longer exposure time and serial sampling were usually required to ensure equilibrium conditions.…”
Section: Theoretical Considerations and Methodologiesmentioning
confidence: 99%
“…2 Other sediment characteristics, however, such as particle size 3 and types of OC, e.g. black carbon and pigments, [4][5][6] can also play a critical role in the bioaccumulation of sediment-associated HOCs. As a result, simply normalizing HOC concentrations to sediment OC may not fully compensate for the differences among sediments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, carbonaceous materials in sediments or soils are considered super sorbents for HOCs and have the ability to markedly alter the bioavailability of HOCs (Cornelissen et al, 2005). The effect of different types of black carbon on the bioavailability of HOCs has been investigated with the aid of disposable SPME fibers (Conder and La Point, 2005; Jonker et al, 2007; Pehkonen et al, 2010; Yang et al, 2009ab). In the case of carbon nanomaterials, the availability of HOCs has also been found to correlate closely with C free measured by SPME fibers (Cui et al, 2011, Hu et al, 2008), but exceptions exist.…”
Section: Passive Samplers For Measuring Freely Dissolved Concentramentioning
confidence: 99%